2013
DOI: 10.2463/mrms.2012-0094
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Scan Parameters for T1-FLAIR Imaging at 1.5 and 3T using Computer Simulation

Abstract: Purpose: We attempted to optimize scan parameters for T 1 -weighted ‰uid-attenuated inversion recovery (T 1 -FLAIR) sequence at 3 and 1.5 tesla (T) using computer simulation.Methods: We measured the T 1 and T 2 relaxation time values (T 1 v and T 2 v) of gray (GM) and white matter (WM) at 3 and 1.5T, generated computer-simulated T 1 -FLAIR (CS-T 1 -FLAIR) images using those values, and compared the simulated and actual T 1 -FLAIR images to verify the contrast reliability of our computer simulation. We mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…T 1 and T 2 * values for WM and GM estimated using QPM were evaluated through comparison with reference values. 13 , 14 To evaluate the QSM obtained using QPM, we examined the correlation with QSM acquired at the same spatial resolution as QPM and the same imaging conditions as in the reference: FA = 15 degrees, TR = 35 ms, and TE = (7.0, 11.6, 16.2, 20.8, 25.4, and 30.0) ms. 15 …”
Section: Methodsmentioning
confidence: 99%
“…T 1 and T 2 * values for WM and GM estimated using QPM were evaluated through comparison with reference values. 13 , 14 To evaluate the QSM obtained using QPM, we examined the correlation with QSM acquired at the same spatial resolution as QPM and the same imaging conditions as in the reference: FA = 15 degrees, TR = 35 ms, and TE = (7.0, 11.6, 16.2, 20.8, 25.4, and 30.0) ms. 15 …”
Section: Methodsmentioning
confidence: 99%
“…6 For operation at 3 T, longer values of TR, TI and TE are generally employed, e.g. 2675, 2000 and 17 ms. 1 Longer TRs are acceptable for the T 1 FLAIR sequence at 3 T, and, by mathematical simulation, Oda et al 7 showed a wide but optimum range of TRs between 2400 and 3900 ms at 3 T. Although T 1 FLAIR sequences are commonly used in the spine and are said to provide excellent delineation of CSF, bone and disc bone interfaces at 3 T, [1][2][3] to date there has been little critical evaluation of their performance. Most of the articles have dealt with the role of T 1 FLAIR sequence in imaging degenerative disease of the lumbar spine, 5,8 wherein suppression of the abundant quantity of CSF within the lumbar thecal sac would allow for greater tissue contrast and improved image quality.…”
mentioning
confidence: 99%